The Role Of Mindfulness To Reduce Anxiety Facing Muhafadzoh In Female Students Of Islamic Boarding School X - Siti Ratu Syakira Azzahra Candra Putri; Zahro Varisna Rohmadani (Green Publisher Indonesia, 2024)
The aim of this research is to describe the role of mindfulness by using relaxation techniques to reduce the level of anxiety facing muhafadzoh in female students at Madrasah Mu'allimin Mu'allimat Islamic Boarding School X. This research uses a quasi-experimental method. The subjects of this research were female students of Madrasah Mu'allimin and Mu'allimat Pondok Pesantren The data collection technique uses a scale results sheet in the form of a questionnaire while data analysis uses non-parametric Mann-Whitney U. Based on the research results, a 2-tailed asymp sig value of 0.00 < 0.05 is obtained, which indicates that the application of Mindfulness has a significant impact on the variable. observed, namely the level of anxiety. These findings consistently support the research hypothesis which suspects that Mindfulness intervention will be effective in reducing anxiety levels in female students at Islamic Boarding School X.